بنية الأحواض المائية النهرية ومناخها في إقليم الساحل والجبال الساحلية السورية "أنموذج حوض نهر الصنوبر" - حليمة عبد الكريم (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يتناول البحث دراسة بنية الأحواض المائية النهرية في إقليم الساحل والجبال الساحلية السورية ومناخها، وقد دُرِس حوض نهر الصنوبر كأنموذج للبحث ، وفي هذا السياق فإن بنية الحوض بنية رسوبية حلقية تعود في غالبيتها للزمنين الثاني والثالث، فتغلب تشكيلة الجوراسي والكريتاسي على الجزء الأعلى منه، وعلى الجزء الأوسط ترسبات الباليوجين والنيوجين، أما رسوبيات الرباعي فتظهر في أدنى الحوض، لكن تتداخل تشكيلة الجوراسي مع الكريتاسي مع الباليوجين في كثير من مواقع الحوض بسبب التخلع والنهوض الناجمين عن العمل التكتوني وفعاليات الحت النشطة هنا. وتتوضع بنية الحوض المورفولوجية بين مستويات ثلاثة، تتدرج من سطح البحر إلى ارتفاع 1562 م في قمة جبل النبي متى. وهذا يفرض على السكان صعوبة في التحرك ضمن الحوض بسبب بنيته التضريسية المتراصة الوعرة الخشنة. وقد استُخدِمت أدوات البحث والقوانين اللازمة لبيان بنية الحوض. وتبين الدراسة أنّ مناخ الحوض غير منتظم رطوبياً خاصّةً، فكميات الأمطار متذبذبة من سنة لأخرى، وتزداد فروقاً وكماً مع عامل الارتفاع، فمتوسطها السنوي في صلنفة 1225.9 مم, بينما في بوقا الساحلية المنخفضة 809.7 مم، إذ إن معامل ارتباط بيرسون بين الأمطار وعامل الارتفاع 0.8961 شديد، وتبين أن كمية الأمطار تراجعت في الفترة الأخيرة عن معدلاتها الطبيعية بنسبة 15.8%. بينما معدلات درجات الحرارة في الحوض تبقى معتدلة محافظة. ويتضمن البحث الاستنتاجات والتوصيات التي تم التوصل إليها. وينتهي البحث بقائمة للمراجع العربية والأجنبية. This study deals with the structure and climate of catchments in the Syrian coastal and mountainous region, focusing on the catchment of Al-Sanoubar River. The study shows that this catchment has sedimentary structure dating back to the second and third geological periods, with the upper part having Jurassic and Cretasic formations, and the middle part having Polygenic and Newgenic sediments. Sediments relating to the Quarterly appear in the lower part of the catchment. However, the Jurassic, Cretasic and Polygenic formations intermingle in many sites of the catchment due to ruptures and rise resulting from tectonic action. The morphology of the catchment has three levels with gradual heights, starting from sea level up to 1562m (Prophet Mata’a’s peak). This morphological structure has significant effects on the lives of people in the area. Relevant methods, maps, and data are used in this study. This paper finds out that the Mediterranean climate is irregular in some elements. For example, precipitation varies from one year to another and increases depending on height. Its annual average in Slunfeh is 1225.9 mm, while in Boukah is 809.7mm. Applying Pearson’s law shows a strong coefficient correlation of 0.8961. This study also finds out that while precipitation has recently decreased in rate of up to 15.8 %, the average of temperature in the catchment remains moderate. The study ends with some conclusions and recommendations.